2013
DOI: 10.1177/1363461513501709
|View full text |Cite
|
Sign up to set email alerts
|

The expression of depression among Javanese patients with major depressive disorder: A concept mapping study

Abstract: In this study, we explored the presentation of clinical depression in Java, Indonesia. Interviews were conducted with 20 Javanese patients (male and female) with major depressive disorder from both lower and higher socioeconomic levels. The recruited participants came from provincial and private mental health hospitals in the cities of Solo, Yogykarta (Jogja), Jakarta, and Malang on the island of Java, Indonesia. Concept mapping methodology using multidimensional scaling and hierarchical cluster analysis was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…Furthermore, a specialist strongly suggested not using the word ‘depression’ to avoid stigma, with the term ‘mood changes’ being preferable instead. This suggestion is in line with previous findings in which the experience of depression was expressed in many forms and terms by Javanese [ 50 ]. This means that an understanding of the personal and cultural terms should also be considered in choosing or adapting an identification tool.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, a specialist strongly suggested not using the word ‘depression’ to avoid stigma, with the term ‘mood changes’ being preferable instead. This suggestion is in line with previous findings in which the experience of depression was expressed in many forms and terms by Javanese [ 50 ]. This means that an understanding of the personal and cultural terms should also be considered in choosing or adapting an identification tool.…”
Section: Discussionsupporting
confidence: 93%
“…Morevoer, a major criticism of using secondary social media data in this type of research is related to the uncertainty of the characteristics of the online respondents, in particular the lack of clinical confirmation of diagnosis [ 18 ]. Another study has demonstrated comparability in the findings derived from online blogs and face-to-face interviews, however [ 20 ]. It would be important to replicate this study using subjects with a clinically confirmed diagnosis and compare their insights with those collected from social media sources to enable conclusions to be drawn around the “representativeness” and “validity” of secondary online data versus primary, prospective data.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations and survey findings about challenges with the sorting phase of GCM is reflected in other GCM studies [8, 11]. One study using GCM to understand barriers to cancer screening in formerly homeless women with serious mental illness excluded 11 of 27 sorts (41%) in their analysis due to sorting statements based on importance, using a “miscellaneous” pile, or only sorting into two piles [8].…”
Section: Discussionmentioning
confidence: 61%